Digital Da'wah Semiotics: Content Analysis of Artificial Intelligence on Abu Marlo Instagram - Muhammad Syahrul Wafda; Warto Warto; Gilman Habibi (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
This research aims to analyze several da'wah content on Abu Marlo's Instagram account created using Artificial Intelligence (AI). The approach used is descriptive qualitative. Analysis using Roland Barthes' semiotics. In this discussion, the author analyzes several images from Abu Marlo's Instagram account using denotative, connotative, and mythic meanings. The research findings indicate that the image content used in Abu Marlo's preaching not only serves as a visual medium but also carries strong symbolic and ideological meaning. Therefore, it can be concluded that Islamic preaching through image content on Abu Marlo's Instagram account is an effective form of visual communication in conveying Islamic values contextually and attractively. This research shows that a semiotic approach can reveal layers of meaning in digital preaching content. This is also related to contributions in the field of communication in the digital era, where technological developments are currently accelerating, leading to the emergence of the term